Effects of the COVID-19 pandemic on diet and physical activity and the possible influence factors among Saudi in Riyadh - Almousa, Lujain Abdulaziz; Alagal, Reham Ibrahim (Frontiers in Nutrition, 2022)
Background/Aim: The COVID-19 pandemic has been spreading worldwide, causing an enormous influence on our lifestyle and health through social distancing and home confinement. This study aims to investigate the impact of COVID-19 on physical activity and diet and to discover the possible influence factors among residents aged ≥13 years in Riyadh, Kingdom of Saudi Arabia. Materials and Methods: Using an online survey, we collected data from 2651 participants. The Google online questionnaire was conducted from 23 April 2020 to 6 May 2020. The survey included questions on the demographic characteristics of the respondents (gender, age, education, economic income, occupation), anthropometric information, physical activity, and diet behaviour during the COVID-19 lockdown. Results: A total of 2651 respondents were included in the study: 23.3% male and 76.6% female. 31% of the participants were overweight, and 14.3% were obese. The data showed that the COVID-19 lockdown has had a negative effect on physical activity and maintaining a healthy diet (p=0.023*)( p=0.000**) respectively. During the confinement period, (32.3%) who were following a healthy diet were unable to maintain it, with males being affected more than females (42.7%, 29,3%, respectively) (P=0.004) (and those most impacted were aged between 21 to 29 years (38.0%) (P=0.046). Moreover, 59.5% of males significantly failed to continue to exercise during the confinement period compared with females who were persistent in exercising (P= 0.01). With regard to age, females aged less than 40 years increased their exercise rate by about 23.4% compared with a decrease in exercise rate by 25.7% among males of the same age group and above (P=0.000). Moreover, the results indicated that 40.5% of the subjects experienced an increase in their weight. However, there was no significant impact on body mass index a 51% of participants were overweight and obese. While home confinement is a precaution for public health, this study provided data . Conclusion: physical activity and diet habits are declining as the COVID-19 pandemic is ongoing.